Implementasi Metode Rapid Application Development (RAD) Pada Sistem Arsip Digital Akreditasi Sekolah Berbasis Website (Studi Kasus : SMP Muhammadiyah 29 Depok) - Azriel Akbar Herdiansyah; Maulana Ardhiansyah (Shofanah Media Berkah, 2023)
The study aims to implement the Rapid Application Development (RAD) method on a website-based school accreditation digital archive system, with a case study at SMP Muhammadiyah 29 Depok. The RAD method was chosen because it can produce applications quickly and effectively, and allows users to provide fast and continuous feedback during the development process. The research was conducted using a qualitative approach, with data collection techniques through observation, interviews, and documentation. The data obtained were then analyzed using descriptive analysis methods. The result showed that the implementation of RAD method on a website-based school accreditation digital archive system at SMP Muhammadiyah 29 Depok can increase the efficiency and effectiveness of the application development process, so that development time is cut and development costs can be reduced. In addition, the RAD method also allows users to provide fast and continuous feedback during the development process, so that the resulting applications are more in line more in live with user needs. In conclusion, this study shows that the implementation of the Rapid Application Development method on a website-based school accreditation digital archive system at SMP Muhammadiyah 29 can increase the efficiency and effectiveness of application development, as well as produce benefits to application developers, schools, and related parties in developing a website-based school accreditation digital archive system.